Effects on profits and risks of hedging hogs in the futures market - J H McCoy; R V Price; R E Solomon (Kansas Agricultural Experiment Station Research Reports, 1976)
Erratic hog prices in recent years have compounded management problems. As a result, interest has increased in ways of tying down prices before the hogs are ready for market. This report presents results of a study of one approach to the problem -- hedging in the futures market.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Profits; Hedging; Futures markets